Spectroscopic and Chromatographic Characterization of Two Isomeric Cathinone Derivatives: N-Butyl-Norbutylone and N-Ethylhexylone - Marcin Rojkiewicz; Piotr Kuś; Josef Jampilek; Andrzej Bąk; Violetta Kozik (Molecules)
In this study, two isomeric cathinone derivatives, N-butyl-norbutylone and N-ethylhexylone, seized on the illicit drug market in Poland, were described and characterized by various instrumental analytical methods. The compounds were characterized by electrospray ionization mass spectrometry, high-resolution mass spectrometry, gas chromatography–mass spectrometry, and nuclear magnetic resonance spectroscopy. The two investigated compounds were confirmed as 1-(2H-1,3-benzodioxol-5-yl)-2-(butylamino)butan-1-one and 1-(2H-1,3-benzodioxol-5-yl)-2-(ethylamino)hexane-1-one, both of which were cathinone derivatives available on the new psychoactive substances (NPS) market. The obtained analytical data should be useful for forensic and toxicological purposes for quick and reliable compound identification.